Phonetic Cohesion in the Rhyme Structure of the Qur'an: A Phonological Analysis of Sound Patterns in Surah Al-Inshiqaq - Habibi, Nicolas (Institut Agama Islam Negeri Curup, 2025)
The purpose of this study is to examine phonetic cohesion in the rhymes of Surah Al-Inshiqaq from a phonological perspective to understand how sound patterns in rhymes contribute to text cohesion, aesthetic appeal, and emphasis of the message in the Holy Qur'an. Using generative phonology as the theoretical framework, this cognitive-linguistic analysis employs a descriptive-qualitative method to investigate both segmental features (consonants and final vowels) and suprasegmental features (intonation and rhythm). The findings reveal strong internal cohesion through frequent repetition of final phonemes such as /a/ and /qa/, which creates a structured rhyme scheme that enhances musicality and facilitates memorization. This phonetic effect enriches the literary beauty as well as the rhetorical and spiritual impact of the text, particularly reinforcing its eschatological themes. The study offers practical insights for phonological analysis of religious texts, Qur'ānic recitation, and linguistic interpretation pedagogy. Notably, this approach integrates modern linguistic theories into the interdisciplinary discourse on Qur'ānic stylistics, bridging linguistics and Islamic studies.